2012
DOI: 10.1016/j.ijrobp.2011.05.011
|View full text |Cite
|
Sign up to set email alerts
|

A Beam-Specific Planning Target Volume (PTV) Design for Proton Therapy to Account for Setup and Range Uncertainties

Abstract: Purpose To report a method for explicitly designing a planning target volume (PTV) for treatment planning and evaluation in heterogeneous media for passively scattered proton therapy and scanning beam proton therapy using single-field optimization (SFO). Methods and Materials A beam-specific PTV (bsPTV) for proton beams was derived by ray-tracing and shifting ray lines to account for tissue misalignment in the presence of setup error or organ motion. Range uncertainties due to inaccuracies in CT-based range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
107
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(109 citation statements)
references
References 20 publications
1
107
0
1
Order By: Relevance
“…Strictly speaking, the PTV concept commonly used in photon therapy cannot be directly used for proton therapy because the range uncertainties are beam-direction-specific (18). However, beam-specific PTVs (bsPTVs) (19) are not available in our clinical treatment planning system for IMPT. Nevertheless, we used the PTV concept to manage delivery uncertainties for plans with a non-parallel-opposed beam arrangements (20).…”
Section: Methodsmentioning
confidence: 99%
“…Strictly speaking, the PTV concept commonly used in photon therapy cannot be directly used for proton therapy because the range uncertainties are beam-direction-specific (18). However, beam-specific PTVs (bsPTVs) (19) are not available in our clinical treatment planning system for IMPT. Nevertheless, we used the PTV concept to manage delivery uncertainties for plans with a non-parallel-opposed beam arrangements (20).…”
Section: Methodsmentioning
confidence: 99%
“…Since conventional geometric margins are not suitable for PT [Park et al, 2012b], margins based on range changes were used. Another trial comparing photon to proton therapy in NSCLC patients also used different PTV definitions to incorporate range changes [Roelofs et al, 2012].…”
Section: Range Margins and Motion Mitigationmentioning
confidence: 99%
“…However, scanning beam proton therapy does not require such beam-specific hardware, therefore lacks the method of appropriately accounting for the uncertainties in order to provide adequate target coverage. Recently, Park et al 10 have demonstrated that beam specific planning target volume (bsPTV) could take into account of both setup and range uncertainties for scanning beam plans generated with single field optimization. 10 However, bsPTV is not applicable to the multifield optimized IMPT plans.…”
Section: Introductionmentioning
confidence: 99%